HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN PENERAPAN PEMBERIAN OBAT KEMOTERAPI PADA PASIEN CA MAMAE DI RUMAH SAKIT MURNI TEGUH MEDAN - Kristina Buaton; Seriga Banjarnahor (Universitas Murni Teguh, 2026)
Breast cancer is one of the leading causes of death in women worldwide. One of the main treatment methods is chemotherapy, which requires high precision and expertise from nurses to ensure the proper and safe use of chemotherapy drugs. Nurse knowledge is crucial. The use of chemotherapy drugs that do not meet standards can pose a risk to patient safety. This study aims to determine whether there is a relationship between nurse knowledge and the implementation of chemotherapy drug administration in breast cancer patients at Murni Teguh Hospital, Medan. This quantitative study used a cross-sectional method. This study used a total sampling technique and involved 44 nurses working in the oncology ward. The research instrument used a knowledge and implementation questionnaire. The results of the study were used to analyze univariate and bivariate data using the Spearman's Rho test. 36 of the participants, or 81.8 percent, showed a good level of knowledge, and 35 people, or 79.5 percent, showed the correct application of chemotherapy drugs. The Spearman's Rho test results showed a strong and significant positive relationship between nurses' knowledge and the application of chemotherapy drugs in patients with breast cancer at Murni Teguh Hospital, Medan, with a ρ value of 0.846 and a p-value of <0.001. Hospitals are expected to improve nurse training and education to protect patients and provide better nursing services.